Balancing act: How community measures shape environmental risk perceptions and preventive behaviours during the COVID-19 pandemic - Li, Zonghan; Zhang, Qiang; Wang, Chunyan; Zhang, Fang; Liu, Yi; Zhang, Lei; Xie, Dan (Environmental impact assessment review, 2025)
Residential communities play a crucial role in decelerating public health crises. The perceived risk of viral infection via environmental media may change dynamically, leading to heterogeneous interactions between individuals and communities intended to prevent an epidemic. However, it remains unclear how community-level measures influence individual preventive behaviours. Taking COVID-19 as an example, three rounds of surveys were conducted across different stages of the pandemic in Beijing, China, from March 2020 to August 2021. The results show that individuals maintained high levels of environmental risk perceptions (3.97 out of 5 on average) and a high likelihood of engaging in preventive behaviours (72.1 % on average) across different stages. Droplet- and aerosol-related environmental risk perceptions and preventive behaviours were promoted most actively in environmental media and exceeded perceptions and behaviours related to buildings' sanitary plumbing systems and wastewater by 25.5 %. By establishing a series of structural equation models, we analysed the decision-making process for preventive behaviour influenced by environmental risk perceptions (average β = 0.32). Individual mentalities on community measures mediated this decision-making process by 16.7 % ∼ 25.7 %. Additionally, we found that the mediating effects increased with the stringency of community measures and varied across different environmental media. The findings highlight the significance of community-level governance in reshaping individuals' environmental risk perceptions and preventive behaviours to enable more effective public health strategies and enhance the resilience of cities. •Individuals' preventive behaviours (PBs) are influenced by the severity of COVID-19.•PBs against droplet & aerosol are most active among environmental medias.•Environmental risk perceptions positively affect PBs and individually varied.•Community COVID-19 preventive measures mediate PB decisions by 17 % ∼ 26 %.